Intraoperative Radiotherapy in Brain Malignancies: Indications and Outcomes in Primary and Metastatic Brain Tumors - Cifarelli, Christopher P.; Jacobson, Geraldine M. (Frontiers in Oncology, 2021)
Despite the continued controversy over defining an optimal delivery mechanism, the critical role of adjuvant radiation in the management of surgically resected primary and metastatic brain tumors remains one of the universally accepted standards in neuro-oncology. Local disease control still ranks as a significant predictor of survival in both high-grade glioma and treated intracranial metastases with radiation treatment being essential in maximizing tumor control. As with the emergence and eventual acceptance of cranial stereotactic radiosurgery (SRS) following an era dominated by traditional radiotherapy, evidence to support the use of intra-operative radiotherapy (IORT) in brain tumors requiring surgical intervention continues to accumulate. While the clinical trial strategies in treating glioblastoma with IORT involve delivery of a boost of cavitary radiation prior to the planned standard external beam radiation, the use of IORT in metastatic disease offers the potential for dose escalation to the level needed for definitive adjuvant radiation, eliminating the need for additional episodes of care while providing local control equal or superior to that achieved with SRS in a single fraction. In this review, we explore the contemporary clinical data on IORT in the treatment of brain tumors along with a discussion of the unique dosimetric and radiobiological factors inherent in IORT that could account for favorable outcome data beyond those seen in other techniques.